Case Report First-in-Man Method Description: Left Ventricular Unloading With iVAC2L During Veno-Arterial Extracorporeal Membrane Oxygenation: From Veno-Arterial Extracorporeal Membrane Oxygenation to ECMELLA to EC-iVAC® - Tschöpe, Carsten; Alogna, Alessio; Faragli, Alessandro; Klingel, Karin; Schmidt, Gunther; Heilmann, Torsten Wolfgang; B. Bastos, Marcelo; Spillmann, Frank (Frontiers in Cardiovascular Medicine, 2020)
Veno-arterial extracorporeal membrane oxygenation (V-A ECMO) is increasingly used in bi-ventricular failure with cardiogenic shock to maintain systemic perfusion. Nonetheless, it tends to increase left ventricular (LV) afterload and myocardial oxygen demand. In order to mitigate these negative effects on the myocardium, an Impella CP® (3.5 L/min Cardiac Output) can be used in conjunction with V-A ECMO (ECMELLA approach). We implemented this strategy in a patient with severe acute myocarditis complicated by cardiogenic shock. Due to a hemolysis crisis, Impella CP® had to be substituted with PulseCath iVAC2L®, which applies pulsatile flow to unload the LV. A subsequent improvement in LV systolic function was noted, with increased LV ejection fraction (LVEF), LV end-diastolic diameter (LVEDD) reduction, and a reduction in plasma free hemoglobin. This case documents the efficacy of iVAC2L in replacing Impella CP as a LV vent during V-A ECMO, with less hemolysis.